Mechanism of cavitation-induced atomization in two-dimensional nozzles - Muhammad Ilham Maulana; . Jalaluddin (Syiah Kuala University, 2012)
It has been pointed out that cavitation, i.e., super cavitation regime may occur in a nozzle of pressure atomizers, and may influence atomization of a liquid jet discharged from the 2D nozzle. Once we clarify the mechanism of atomization induced by the supercavitation, we will be able to develop new atomizers in which the atomization mechanism is utilized more efficiently. Hence, this study has been conducted to clarify the mechanism in the 2D nozzle. As a result, the following conclusions are obtained: (1) The frequency of the shedding and collapse of cavitation clouds in the supercavitation regime agrees with that of strong turbulence near the exit; (2) When the trace of a cavitation cloud comes out of the 2D nozzle, a ligament is formed at the liquid jet interface; (3) Strong turbulence is produced by the collapse of cavitation clouds near the exit of the 2D nozzle.and induces ligament formation, which, in turn, causes liquid jet atomization.